SAREKAT ISLAM (SI) GERAKAN PEMBARUAN POLITIK ISLAM - Ismail Usman (Institut Agama Islam Negeri (IAIN) Manado, 2017)
Abstract. The birth of a politically oriented Sarekat Islam with the forerunner of business oriented Islamic Trade Sarekat was inseparable from the strong motivation to implement Islamic teachings in various aspects. Not only limited to worship rituals, but also need to be translated into the midst of other aspects, especially at that time the condition of the Indonesian people was under Dutch colonialism, so Islamic political movements were a mystery and focus. Using Islamic labels in organizations that allow positive responses everywhere to participate in this organization. In this paper the author wants to know what the Sarekat Islam has been doing in carrying out political relations and anything that contributes to the movement of Indonesian nationalism with Islam as a basic effort and whatever efforts are needed in upholding these noble ideals. Keywords: Politics, Islam, Islamic Trade Law, Nationalism. Abstrak. Lahirnya Sarekat Islam yang berorientasi politik dengan cikal bakal dari Sarekat Dagang Islam yang berorientasi bisnis tampaknya tidak lepas dari motivasi kuat untuk mengimplemantasikan ajaran-ajaran Islam dalam berbagai aspeknya. Bukan saja terbatas pada ibadah ritual, tapi juga perlu dijabarkan ke tengah- tengah masyarakat aspek-aspek lain, lebih-lebih pada waktu itu kondisi bangsa Indonesia sedang berada di bawah tekanan kolonial Belanda, maka kehadiran gerakan politik Islam merupakan tuntutan dan keharusan. Menggunakan label Islam dalam organisasi politik ini mungkin dimaksudkan untuk menarik respons masyarakat muslim di mana saja untuk ikut serta berpartisipasi dalam organisasi ini. Dalam makalah ini penulis ingin membahas sejauh mana kiprah Sarekat Islam dalam melakukan pembaruan politik dan apa sumbangsinya terhadap gerakan nasionalisme Indonesia dengan Islam sebagai ajaran dasar serta kendala-kendala apa yang dihadapi dalam menegakkan cita-cita luhur ini. Keywords: Politik, Islam, Sarekat Dagang Islam, Nasionalisme